Organizational Changes and Development in Islamic Education Institutions Post Covid-19 Pandemic - Cecep Nikmatullah; Badrudin Badrudin; Anis Fauzi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2022)
The purpose of this research is the importance of organizational change and development in improving the organization's ability to adapt to environmental changes. This qualitative research with a literature approach is sourced from various literatures; journal articles, reference books, textbooks, and related documents. The findings show that organizational change and development in Islamic educational institutions after the COVID-19 pandemic can be designed through three aspects; changing attitudes/values, modifying behavior, and encouraging structural and policy changes. So it is necessary to develop organizational leadership to influence people to behave in accordance with the expectations of the leader, and adapt to the strategic environment of the organization. Post-pandemic, Islamic educational institutions must be oriented to three things; the use of Islamic reasoning based on the Qur'an and hadith, human resources (human needs), and technology. Online learning has a positive impact, teachers and students no longer rely on face-to-face learning because they are used to doing distance learning. The challenges of Islamic Educational Institutions in overcoming organizational change and development are; (1) consider the fundamental role. (2) pay attention to the function of the instrument as an educational tool. (3) there is a constructive role. The three roles are an effort to integrate components to realize Islamic education, make changes and organizational development on government policies through the nature, roles, responding to challenges and developments as well as post-pandemic technology